Sexual behaviour of lesbians and bisexual women. Issue 2 (1st April 2003) - Bailey, J V; Farquhar, C; Owen, C; Whittaker, D
Abstract : Objectives: To provide data about the sexual histories of a large sample of lesbians and bisexual women, to inform those who provide health care or carry out research with women who may be sexually active with other women. Design: Cross sectional survey. Setting/subjects: 803 lesbians and bisexual women attending, as new patients, lesbian sexual health clinics, and 415 lesbians and bisexual women from a community sample. Main outcome measures: Self reported sexual history and sexual practice with both male and female partners. Results: 98% of the whole sample gave a history of sexual activity with women, 83% within the past year, with a median of one female partner in that year. 85% of the sample reported sexual activity with men; for most (70%) this was 4 or more years ago. First sexual experience tended to be with a man (median 18 years old), with first sexual experience with a woman a few years later (median 21 years). Oral sex, vaginal penetration with fingers, and mutual masturbation were the most commonly reported sexual practices between women. Vaginal penetration with penis or fingers and mutual masturbation were the most commonly reported sexual activities with men. Conclusions: These data from the largest UK survey of sexual behaviour between women to date demonstrate that lesbians and bisexual women may have varied sexual histories with both male and female partners. A non-judgmental manner and careful sexual history taking without making assumptions should help clinicians to avoid misunderstandings, and to offer appropriate sexual health advice to lesbians and bisexual women.